A 10-Year Prevalence Survey and Clinical Features Analysis of Pressure Injury in a Tertiary Hospital in China, 2009–2018. (March 2021) - Zhao, Jing; Zhang, Liu-Xin; Zhong, Yu-Ling; Hu, Xin-Yu; Cheng, Yang; Zhou, Yu-Feng; Wang, Jie
ABSTRACT: OBJECTIVE: To describe the 10-year prevalence of pressure injury (PI) in a tertiary hospital in China and determine the clinical characteristics of inpatients with PI. METHODS: The authors performed a retrospective analysis of PI cases extracted from the electronic health record of a tertiary hospital. The trend of PI prevalence over 10 years was described by estimating the average percent change (EAPC). Comorbidities were described with the Charlson Comorbidity Index (CCI). The clinical characteristics of PI were described using the number of cases and composition ratio. RESULTS: The overall prevalence of PI was 0.59% (5, 838/986, 404). From 2009 to 2018, the rate increased from 0.19% to 1.00% (EAPC = 22.46%). When stage I PIs were excluded, the prevalence of PI ranged from 0.15% to 0.79% (EAPC = 21.90%). The prevalence of hospital-acquired PI was 0.13%. Prevalence increased with age ( P trend < .001) and was significantly higher in men than women ( P < .001). Patients with PI were more widely distributed in the ICU (20.58%), vasculocardiology department (11.73%), gastroenterology department (10.18%), and OR (8.29%). Of patients with PI, 71.3% had a CCI score 4 or higher. CONCLUSIONS: The PI prevalence in the study facility increased rapidly over the study period. Pressure injuries among patients in the gastroenterology department and in the community deserve more attention. The CCI may be a good indicator for PI risk assessment.